Augmented reality in the news discourse on La Palma volcano: The examples or TVE and RTVC - Herrero de la Fuente, Mercedes; Jiménez Narros, Carlos; Puelles Gutiérrez, Miriam (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Augmented reality expands the possibilities of news discourse. We address its use in the news pieces of La 1 de TVE and RTVC on the eruption of the Cumbre Vieja volcano in La Palma, whose activity is maintained for almost three months (September-December 2021). We applied to an analysis matrix to the pieces produced with this technology to find out their typology and functionality. The research is completed with six in-depth interviews with experts and professionals from both broadcasters. We conclude that RTVC includes this resource in its narrative more frequent and makes better use of it.